Multimodal MRI evaluation of parkinsonian limbic pathologies - Wang, Ernest W. (Neurobiol Aging, 2019)
Previous multimodal magnetic resonance imaging (MRI) studies of parkinsonian syndromes have focused primarily on motor-related basal ganglia structures. The present study investigated MRI changes in non-motor-related limbic structures in 35 Parkinson’s disease (PD), 16 multiple system atrophy parkinsonian subtype (MSA-P), 17 progressive supranuclear palsy (PSP), and 37 control subjects. Mean diffusivity (MD), fractional anisotropy (FA), transverse relaxation rate (R2*), quantitative susceptibility mapping, and volume measurements were obtained from the amygdala, hippocampus, and nucleus accumbens (NAc) to examine differences between groups, and to test for associations with clinical scores. Compared to controls, PD subjects had lower NAc volume; MSA-P subjects had higher NAc R2*; PSP subjects had higher amygdala and hippocampus MD, and lower hippocampus FA (ps ≤ 0.008). Among parkinsonian subjects, amygdala and hippocampus MD associated positively with Unified Parkinson's Disease Rating Scale (UPDRS) non-motor and activities of daily living (ADL) scores (ps ≤ 0.005). Together, these findings support the inclusion of limbic structures in future MRI studies of parkinsonian syndromes.